Optimization of electrospinning process & parameters for producing defect-free chitosan/polyethylene oxide nanofibers for bone tissue engineering. Issue 6 (12th April 2020) - Singh, Yogendra Pratap; Dasgupta, Sudip; Nayar, Suprabha; Bhaskar, Rakesh
Abstract: Chitosan (CS) nanofibers were electrospun from aqueous chitosan solution using concentrated acetic acid solution as a solvent. Polyethylene oxide (PEO) with varying weight content from 10- 60 wt% was mixed with chitosan solution that acted as a plasticizer to improve spinability of the prepared chitosan solution. With the increase in PEO content from 10-50 wt% the viscosity of the resultant CS/PEO solution was decreased from 0.938 Pa-s to 0.272 Pa-s, whereas higher the concentration of acetic acid lower was the surface tension of resultant chitosan solution. It was found beadless nanofibrous chitosan mat was obtained not less than 85% acetic acid concentration, 50 wt% PEO and at 0.2 wt% NaCl and 5 wt% total polymer concentration. From field emission scanning electron microscopy (FESEM) investigation, it was observed that chitosan fibers with an average diameter of 149 nm were produced at an applied voltage of 22.5 KV, while that varied between 17.5- 25 KV. On the other hand, a minimum of 110 nm of average diameter chitosan nanofiber was obtained at a needle tip to rotor collector distance of 15 cm by the method of electrospining. In terms of solution flow rate, 0.4 mL/h was found to be optimum in obtaining defect-free electrospun fiber with lower average diameter. As a whole, smooth and uniform chitosan nanofibers were obtained from 50/50 CS/PEO solution prepared by using 90% acetic acid and electrospun at 20 kV applied voltage, 15 cm needle tip-to- rotor collector distance with 0.2 mm inner diameter needle and 0.4 mL/h feeding rate. After crosslinking with 1 wt% glutaraldehyde (GTA), the ultimate tensile strength and Young's modulus of chitosan scaffold increased upto 9.47 MPa and 147.75 MPa respectively. From MTT assay and alkaline phosphatase expression analysis upto 11 days of cell culture period it was evident that thus prepared electrospun CS scaffolds supported MG 63 cell proliferation and its differentiation into mature osteoblast.